The ovulation assessment of regular cyclic rats following subacute oral administration of monosodium glutamate: An in vivo study - Mahfoudh Almusli Mohammed Abdulghani (GarVal Editorial Ltda., 2022)
Context: The possible toxic effects of monosodium glutamate (MSG) on ovarian functions have not been thoroughly evaluated in contrast to testicular functions. Few studies documented that MSG showed histological alterations. Aims: To investigate the subacute effects of oral MSG (2 g/kg) on estrogen level and numbers of ovulated oocytes and histological changes in ovary of Sprague-Dawley (SD) rats. Methods: Virgin young adult SD female rats with a regular estrous cycle were randomly assigned to either MSG-treated group or control group, and the duration of treatment was 14-16 days for oral administration MSG or vehicle (distilled water), respectively. Results: Oral MSG treatment with doses of 2 g/kg/day showed significantly (p<0.01) reduced numbers of ovulated oocytes in the oviduct, newly formed corpora lutea, large follicles in histology of ovarian sections and attenuated serum estrogen levels. Conclusions: Subacute oral administration of MSG may negatively influence the ovarian function of young female rats via reduction of ovulated oocytes and the attenuation of estrogen level.